Fast Angle Adaption of a MEMS-based LiDAR System. Issue 15 (2019) - Stelzer, Philipp; Strasser, Andreas; Steger, Christian; Garcia, Alberto; Druml, Norbert
Abstract: The amount of Advanced Driver-Assistance Systems (ADAS) in middle-class cars are increasing steadily. Next generation ADAS will take control in fully automated vehicles. Light Detection And Ranging (LiDAR) will be one of the key enablers for highly automated or even autonomous vehicles. The 1D Micro-Electro-Mechanical System (MEMS) Micro-Scanning LiDAR is able to detect obstacles in a predefined Field-of-View (FoV). Future ADAS applications will require to dynamically change FoVs as fast as possible (e.g. quickly switching between long-range narrow FoV and short-range wide FoV). In this paper we introduce a novel system architecture that enables fast angle adaption of a 1D MEMS Micro-Scanning LiDAR System. The system architecture was implemented in an FPGA prototype to prove its feasibility and to evaluate its performance.